Mesenchymal Stem Cell Derived Extracellular Vesicles in Aging - Boulestreau, Jérémy; Maumus, Marie; Rozier, Pauline; Jorgensen, Christian; Noël, Danièle (Frontiers in Cell and Developmental Biology, 2020)
Aging is associated with high prevalence of chronic degenerative diseases that take a large part of the increasing burden of morbidities in a growing demographic of elderly people. Aging is a complex process that involves cell autonomous and cell non autonomous mechanisms where senescence plays an important role. Senescence is characterized by the loss of proliferative potential, resistance to cell death by apoptosis and expression of a senescence-associated secretory phenotype (SASP). SASP includes pro-inflammatory cytokines and chemokines, tissue-damaging proteases, growth factors; all contributing to tissue microenvironment alteration and loss of tissue homeostasis. Emerging evidence suggests that the changes in the number and composition of extracellular vesicles (EVs) released by senescent cells contribute to the adverse effects of senescence in aging. In addition, age-related alterations in mesenchymal stem/stromal cells (MSCs) have been associated to dysregulated functions. Loss of functional stem cells necessary to maintain tissue homeostasis likely directly contribute to aging. In this review, we will focus on the characteristics and role of EVs isolated from senescent MSCs, the potential effect of MSC-derived EVs in aging and discuss their therapeutic potential to improve age-related diseases.